Boxing fatalities in relation to rule changes in Japan: secondary data analysis - Teramoto, M.; Cross, C. L.; Cushman, D. M.; Willick, S. E. (The Physician and Sportsmedicine, 2018)
Objectives: To examine whether changing weigh-in from the same day of the match to the day before the match and prohibiting 6-oz gloves are associated with fatalities in boxing matches sanctioned by the Japan Boxing Commission (JBC).